„Tysiąc wierszy”. O poezji Wioletty Grzegorzewskiej tropem Guguł (bądź odwrotnie) - Gralewicz-Wolny, Iwona (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article is devoted to the issue of the relationship between poetry and prose area of Wioletta Grzegorzewska’s literary activity. Nominated for the most important national literary awards and the Man Booker International Prize Guguły (2014) are here interpreted as the work located at the intersection of poetry and prose, in which accumulate two most important qualities of Grzegorzewska’s creativity: a unique sense of observation and sensual imagination. They join in idiom, which the reader will recognize easily, no matter what solution formally propose its author.